The effect of substituents on the reactivity of dichloridotriphenylphosphinoruthenium(II) complexes: kinetic and mechanistic study. Issue 9 (25th June 2021) - Sitati, Meshack K.; Mutua, Gershom Kyalo; Onunga, Daniel O.; Jaganyi, Deogratius; Mambanda, Allen
Abstract: The rates of substitution of chloro ligands from a series of ruthenium(II) complexes, [Ru(κ 3 -L)(PPh3 )Cl2 ] (L = 2, 2′:6′, 2′′-terpyridine, 1 ; 4′-(4-methylphenyl)-2, 2′:6′, 2′′-terpyridine, 2 ; 4, 4′4″-tri-tert-butyl-2, 2′:6′, 2′′-terpyridine, 3 ; 4′-(4-chlorophenyl)-2, 2′:6′, 2′′-terpyridine, 4 ; 4-chloro-2, 2′:6′, 2′′-terpyridine, 5 and 2, 6-bis(2-pyrazolyl)pyridine, 6 ), by thiourea nucleophiles was investigated under pseudo -first-order conditions in methanol as a function of nucleophile concentration and temperature. The chloro ligands were substituted in two steps and the reactivity trend was 4  > 5 > 2  > 1 > 6 . Complexes 2 and 3 having donor substituents on the 2, 2′:6′, 2′′-terpyridine backbone experience a trans -effect making them more reactive than 1 . Complexes 4 and 5 are more reactive than 1 due to enhanced π-back-bonding brought about by electron-withdrawing substituents on their 2, 2′:6′, 2′′-terpyridine backbones. The reactivity of 4 is higher than 5 due to greater electron acceptor-ability of the chlorophenyl substituent than the chloro substituent in 5 . The 2, 6- bis (pyrazolyl)pyridine ligand in 6 retards the reactivity of the complex compared to 1 due to the cis -donor effect of the pyrazole. The reactivity of the complexes is associative for all nucleophiles in step one and only thiourea in step two. The substitution reactions proceed by a steady changeover from an associative interchange mechanism ( I a ) to a dissociative interchange ( I d ) mechanism on increasing steric hindrance. Graphical Abstract: UF0001